Women's political leadership in Islam: A wasatiyyah perspective - Dumiadi, Ayurisya Dominata; Mohd Ramli, Razlini (‘Abqari Journal, 2025)
Before the advent of Islam, women were often marginalized in many civilizations. In ancient Arab civilization before Islam, women's dignity and worth were in the lowest position. Insulting and harsh treatment of women is a tradition that is permitted by society, because they consider the presence of women to be a disgrace and bring disaster to life. Similar conditions occurred in early Greek civilization, where women were also marginalized. This research aims to analyze Islamic views on women's leadership in terms of the Wasatiyyah concept. The research was conducted using qualitative methods with data collection techniques by studying Islamic law based on explanations in the Al-Qur'an, Hadith and examples of Islamic history. This research summarizes that the role of women's leadership in the Wasatiyyah concept is a form of cooperation between men and women in various areas of life, they have an obligation to carry out good orders and avoid evil. This shows that Islam is very cosmopolitan, rahmatan lil 'alamin for all mankind. So women's leadership in Islam is working together with men in cooperation, guidance, attention, nurturing and control in a good way.